EVALUATING SERVICE QUALITY OF SECURITIES TRADING APPLICATIONS: A CASE STUDY OF APPLICATION X USING E-SERVQUAL AND IPA - Villeta Eugenea Chintiander; Katlea Fitriani (Business Administration Department - Universitas Katolik Parahyangan, 2023)
Application X is an application for conducting securities transactions launched by Securities Y. Application X frequently experiences disruptions that hinder transactions, resulting in unsatisfied customers. This study aims to analyze the gap between users' perceptions and expectations of the service quality of the application and provide suggestions for improvement priorities for Application X. The E-Servqual method is used to evaluate user satisfaction with the service quality of the application, while the IPA method is used to determine the improvement priorities. The results show that there are negative gap values between users' expectations and users' perceptions of the service quality of Application X, -1.17. It means that users' perceptions do not meet expectations. The improvement priorities based on the IPA method include the RDN fund top-up process being quick, the application is accessible at any time, resolving user issues quickly, having a clear system failure handling process, displaying an accurate portfolio, making it easier for users to find the desired stock information, displaying accurate transaction fees in the Trade Confirmation, and ensuring the smooth operation of PIN and password authentication.